2011
DOI: 10.4317/medoral.16.e354
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of hemodynamic changes during extraction in controlled hypertensive patients

Abstract: Objective: To evaluate the efficacy and safety of the vasoconstrictor used in local anesthesia during dental extraction in controlled hypertensive patients. Study Design: A prospective observational study was carried out in hypertensive patients (n=97) with a mean age of 60.45±9.60 years. The following parameters were monitored at three different timepoints (before the procedure, 3 minutes after local anesthesia infiltration, and 3 minutes after the operation): blood pressure (diastolic and systolic), heart ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
1
18

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 14 publications
5
27
1
18
Order By: Relevance
“…Despite conducting a more thorough assessment than earlier studies (seven time points), the results of this investigation were similar to the vast majority of cases found in the literature, which generally only assessed some of these variables (Oertel et al, 1999;Malamed et al, 2001;Ogunlewe et al, 2011;Silvestre et al;de Morais et al, 2012a,b). Therefore, the hemodynamic variations in the patients seem to be more closely related to the stress caused by the surgery than the use of a local anesthetic, given that variations were only found between the time points in each of the groups.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Despite conducting a more thorough assessment than earlier studies (seven time points), the results of this investigation were similar to the vast majority of cases found in the literature, which generally only assessed some of these variables (Oertel et al, 1999;Malamed et al, 2001;Ogunlewe et al, 2011;Silvestre et al;de Morais et al, 2012a,b). Therefore, the hemodynamic variations in the patients seem to be more closely related to the stress caused by the surgery than the use of a local anesthetic, given that variations were only found between the time points in each of the groups.…”
Section: Discussionsupporting
confidence: 78%
“…Local anesthetics such as lidocaine and articaine are generally used in combination with a vasoconstrictor to delay the systemic absorption of the anesthetic, thereby prolonging its action and the intensity of the blockage (Silvestre et al, 2011). Vasoconstrictors can cause hemodynamic alterations during the surgical extraction of molars, similar to other factors, such as the patient´s anxiety or stress levels (Tolas et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Chaudhry et al [23] demonstrate that the mean DBP after extraction decreases after tooth extraction which harmonize with results of the current study while there was significant increase seen in the mean SBP of stage-II hypertensive patients (21mmHg) after extraction which contradict this study. The decrease seen in the mean DBP of the present study matches the results of the study done by Abu-Mustafa et al [24], Silvestre et al [22] proclaim no significant changes in SBP and DBP while determining at three time points in those patients who received local anesthesia with vasoconstrictors which support this study. Ogunlewe et al [25] conducted a study on two groups, one received Lidocaine 2% with epinephrine 1:80,000 while other group received plain Lidocaine 2%.…”
Section: Discussionsupporting
confidence: 92%
“…The female to male ratio was 3.88:1 showing high prevalence in females. Silvestre et al [22]. showed that angiotensin II receptor antagonist were the most frequently used medicine by hypertensive patients and prevailed a ratio of 1.9:1 between female and male patients.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid the occurrence of systemic abnormalities and metabolic imbalances during surgery, it is essential for the professional to perform capillary glycemic check before, during and after the procedure, as well as to ensure the correct administration and prescription of trans and postoperative medications 13 . The importance of blood pressure measurement during all appointments, scheduling in the morning in short sessions, verification of the need for complementary sedation, can be emphasized so that the stress factors involved that potentially interfere in the emotional and systemic function of the patient can be reduced 20,21 . It is the responsibility of the dental surgeon to minimize infectious risk factors as well as to manipulate the buccal mucosa in an agile way in order to stimulate a process of rapid and intact healing 5 .…”
mentioning
confidence: 99%